Contact pathway in surgical and transcatheter aortic valve replacement - de la Morena-Barrio, María Eugenia; Corral, Javier; López-García, Cecilia; Jiménez-Díaz, Víctor Alonso; Miñano, Antonia; Juan-Salvadores, Pablo; Esteve-Pastor, María Asunción; Baz-Alonso, José Antonio; Rubio, Ana María; Sarabia-Tirado, Francisco; García-Navarro, Miguel; García-Lara, Juan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Aortic valve replacement is the gold standard treatment for severe symptomatic aortic stenosis, but thrombosis of bioprosthetic valves (PVT) remains a concern. Objective To analyze the factors involved in the contact pathway during aortic valve replacement and to assess their impact on the development of thromboembolic complications. Methods The study was conducted in 232 consecutive patients who underwent: transcatheter aortic valve replacement (TAVR, N = 155), and surgical valve replacement (SAVR, N = 77) (MUVITAVI project). Demographic and clinical data, outcomes including a combined end point (CEP) of thrombotic events, and imaging controls were recruited. Samples were collected 24 h before and 48 h after valve replacement. FXII, FXI and (pre)kallikrein were evaluated by Western Blot and specific ELISA with nanobodies. Results The CEP of thrombotic events was reached by 19 patients: 13 patients presented systemic embolic events and 6 patients subclinical PVT. Valve replacement did not cause FXII activation or generation of kallikrein. There was a significant reduction of FXI levels associated with the procedure, which was statistically more pronounced in SAVR than in TAVR. Cases with reductions of FXI below 80% of basal values had a lower incidence of embolic events during the procedure than patients in whom FXI increased above 150%: 2.7 vs. 16.7%; p: 0.04. Conclusion TAVR or SAVR did not significantly activate the contact pathway. A significant reduction of FXI, was observed, particularly in SAVR, associated with lower incidence of thrombotic events. These results encourage evaluating the usefulness and safety of FXI-directed antithrombotic treatments in these patients.